THE EFFECT OF OPTIMAL CAPITAL STRUCTURE ON PROFITABILITY WITH OPERATIONAL RISK AS AN INTERVENING VARIABLE IN ISLAMIC BANKING OF OIC COUNTRIES - Wiwin Erna Ekawati; Muhammad Said; Ibnu Qizam; Erika Amelia (Referensi Islamika: Jurnal Studi Islam, 2026)
This study empirically examines whether operational risk mediates the relationship between optimal capital structure and profitability in Islamic banking across OIC countries, comparing two competing operationalizations of the leverage target: a bank-specific historical benchmark (Moving Average Leverage Ratio) and an industry benchmark (Industry Median Leverage Ratio). This study uses a quantitative approach with panel-data analysis and purposive sampling of 60 Islamic banks in 10 OIC countries over 2018–2024; removing 43 outlier observations from 420 yields an unbalanced panel of N = 377. Optimal capital structure is measured by the two leverage proxies; operational risk by the ratio of operational risk-weighted assets (ORWA) to total risk-weighted assets (RWA); and profitability by return on assets (ROA). Random Effects panel regression is estimated; although the Hausman test favored Fixed Effects, Random Effects was retained because the industry-median proxy and the institutional controls are (quasi) time-invariant and would be absorbed by Fixed Effects. Mediation is assessed with the Sobel test complemented by cluster-bootstrap confidence intervals, alongside Fixed-Effects and separate-controls robustness checks.  Only one structural result is robust: Industry Median Leverage significantly reduces operational risk (β = −0.1928; p = 0.0001), whereas Moving Average Leverage is not significant. The direct effect of capital structure on profitability is not supported once institutional controls are included, operational risk is not significantly related to profitability, and operational risk does not mediate the capital structure–profitability relationship (all indirect-effect confidence intervals contain zero). Control of corruption is consistently and positively associated with profitability. For managers, the industry-median leverage benchmark can serve as a discipline device for operational risk, not as a proven lever of profitability. For regulators, the results highlight the relevance of institutional quality particularly corruption control for Islamic-bank profitability in cross-country settings. Retaining Random Effects against the Hausman indication, and the regulatory (ORWA/RWA) nature of the operational-risk proxy, are limitations. The contribution is empirical and methodological: the study contrasts two distinct meanings of “optimal” leverage within a single mediation framework, tests operational risk as an explicit mediating channel on a cross-country OIC Islamic-banking panel, and documents a suppression effect of control of corruption on the leverage–profitability association.